Doing corpus linguistics - Csomay, Eniko; Crawford, William J. (New York, NY : Routledge, 2024)
"Doing Corpus Linguistics offers a practical step-by-step introduction to corpus linguistics, making use of widely available corpora and of a register analysis-based theoretical framework to provide students in applied linguistics and TESOL with the understanding and skills necessary to meaningfully analyze corpora and carry out successful corpus-based research"--
Keywords: Corpora (Linguistics); Linguistic analysis (Linguistics); LANGUAGE ARTS & DISCIPLINES / Study & Teaching; LANGUAGE ARTS & DISCIPLINES / General